PENGARUH PERSONAL KNOWLEDGE, ORGANIZATIONAL LEARNING, DAN TEKNOLOGI TERHADAP KINERJA KARYAWAN HOTEL PATRA JASA SEMARANG - Reiza Zarkowi; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2016)
The research was based on globalization era and the growth of knowledge and technology that changed resource-based paradigm into knowledge-based paradigm. The hotel hopes that the application of personal knowledge, organizational learning, and technology will improve the hotel employee performance. Patra Jasa Semarang employee performance has been quite well, but still not optimal. In 2013. The objective of this research was to determine the effect of personal knowledge, organizational learning, and technology on Patra Jasa Semarang employee performance. The research based on explanatory type by collecting data through questionnaires and interviews. The sampling technique using census or saturated. The samples in this research were 108 respondents who are Patra Jasa Hotel Semarang permanent employee. This research uses qualitative and quantitative analysis techniques. The quantitative analysis using validity, reliability test, correlation coefficient, cross tabulation, simple linear and multiple linear regression, determination coefficient, and significance of t test and F test. According to the results of a simple linear regression analysis were found that the variable of personal knowledge, organizational learning, and technology have an effect on employee performance with a coefficient of 0,201, 0,465, and 0,452. Personal knowledge, organizational learning, and technology simultaneously have a significant effect on employee performance with F count > F table (12,004 > 2,691) with a significance score at 0,000 < 0,005.